Profil Kesalahan Siswa pada Materi Satuan Ukuran Ditinjau dari Gaya Belajar Siswa - Ahmad Nizar Rangkuti (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2019)
The purpose of this research was to describe the students’ error in measurement materials in terms of learning style. This is a qualitative descriptive research. The subject of this research was 6 students with each of the two students in visual learning styles, auditory learning styles, and kinesthetic learning style. The research instruments were questionnaire, test, interview, and observations. Data analysis activities were data reduction, data display, and conclusion drawing/ verification. The technique of data analysis used interactive techniques with these three procedures. The result of this research showed that the students’ error with visual learning styles in solving units, size, and time included material concepts errors and the use of mathematical unit; this is because teachers tend to use the lecture method in learning. The students’ errors with auditory learning style in solving unit, size and time included in interpreting data, determining formulas and errors in counting. The cause of this error is not remembering the concept and hurrying in solving math problems. The students’ error with kinesthetic styles in solving unit, size and time included student errors identifying elements and language interpretation, errors in language use, and conceptual errorst.